Grafting of poly (styrene-co-p-chloromethyl styrene) with ethyl methacrylate via atom transfer radical polymerization catalyzed by CuCl/1,2-dipiperidinoethane - Coskun, M; Temüz, MM (John Wiley & Sons Inc, 2003)
Poly(styrene-graft-ethyl methacrylate) graft copolymer was prepared by atom transfer radical polymerization (ATRP) with poly(styrene-co-p-chloromethyl styrene)s in Various compositions as macroinitiator in the presence of CuCl/1,2-dipiperidinoethane at 130 degreesC in N,N-dimethylformamide. Both macroinitiators and graft copolymers were characterized by elemental analysis, IR, H-1 and C-13 NMR, and differential scanning calorimetry. 1,2-Dipiperidinoethane was an effective ligand of CuCl for ATRP in the graft copolymerization. The controlled growth of the side chain provided the graft copolymers with polydispersities of 1.60-2.05 in the case of poly(styrene-co-p-chloromethyl styrene) (62:38) macroinitiator. Thermal stabilities of poly(styrene-graft-ethyl methacrylate) graft copolymers were investigated by thermogravimetric analysis as compared with those of the macroinitiators. (C) 2003 Wiley Periodicals, Inc.
Keywords: graft copolymerization; ATRP; dipiperidino ethane